Mechanical evolution of the rotating biological contactor into the 21st century. - Mba, David (Professional Engineering Publishing, 2003)
This paper presents a review on the evolution of the mechanical design of rotating biological contactors (RBCs) within the UK. The findings documented have been taken from the biggest mechanical survey on RBCs ever undertaken worldwide and focuses on 300 operational units. The paper looks at the main components of the RBC and discusses the evolution of each member. Mechanical deficiencies associated with each design are briefly presented, giving an insight into reasons for improvements. This is the only known document that details changes in design philosophy employed over the last 30 years, with illustrative examples. For the purpose of this review, the mechanical evolution of the RBC is focused on three primary sections: media panel designs, media support structures, and auxiliary support systems including bearings, power units, and transmission systems. It is shown that the evolution of media panels has largely been directed by economies of manufacture and operational requirements. However, advances in the mechanical design of the RBC supporting structure, while dependent on media type, are largely influenced by overcoming known mechanical deficiencies as well as increasing operational life. This paper depicts the current technology and practice of UK-based manufacturers and details reasons for mechanical deficiencies.